Identification of resistant genotypes and representative environments for spot blotch (Biploris sorokiniana) in barley (Hordeum vulgare) - KUMAR, VISHNU; KUMAR, SUDHEER; SINGH, S P; VAISH, S S; DEEPSHIKHA, DEEPSHIKHA; KHAN, J B; KHARUB, A S; SINGH, G P (The Indian Journal of Agricultural Sciences, 2020)
A set of 31 barley genotypes was evaluated at four locations, viz. Kanpur, Pantnagar, Varanasi and Faizabad for two years (2016 and 2017) against spot blotch [Biploris sorokiniana (Sacc.) Shoem.] resistance. The combined analysis of variance revealed significant influence of year (5.64%) and location (18.08%) effects with significant genotypic effects (29.05%). Location-wise, the highest susceptibility was observed at Varanasi (51.61%) followed by Kanpur (19.35%) whereas, the moderately susceptible reactions were obtained at Faizabad (67.74 %) and Kanpur (61.29%) locations. In heritability adjusted GGE biplot analysis, the ratio of (G+G × E)/(E+G+G × E) was estimated as 71.77 % and substantiated usefulness of generated biplots to elucidate resistant and stable genotypes with location discrimination. In AMMI analysis, the initial two principal components (PCs) cumulatively explained 90.7 % of total variation with individual scores of 51.8 % and 38.9 %, respectively. The triangular image of the initial three PCs depicted scattered pattern for disease reaction and varied response for the locations. The weather parameters, viz. maximum temperature, minimum temperature and sunshine hr/day showed strong correlations 0.87**, 0.83** and 0.64* with spot blotch severity. The genotypes, DWRB 180, PL 891 and DWRB 190 were found promising and suggested to be used in future resistance breeding and spot blotch genetic studies. The locations Varanasi and Faizabad were found type 2 discriminative and representative environments for spot blotch.